The Effect of Perceptual – Motor Training on Cognitive Abilities in Children with Mild Mental Retardation - Nahdiah Purnamasari; Nurul Fauziah Arifin; Dian Amaliah Nawir (Faculty of Nursing, Universitas Hasanuddin, 2021)
Introduction: Children with mental retardation are the children who have incomplete mental development, there are an obsctacles during the child’s development that effect their cognitive, motoric, sensory, physical, language, and emotional development. This study aims to determine the effect of perceptual – motor training on changes in cognitive abilities in children with mild mental retardation. Method: This study used a quasi-experimental design with the type of one group pre test and post test. The instrument used montreal – cognitive assessment which consists of 7 cognitive aspects test. The subjects of this study were children with mild retardation from SLB Laniang Makassar who were able to communicate even though the children needed repetition instructions for several times and their aged 10-14 years old. The number of respondent was 17 peoples (out of dropout) and underwent perceptual-motor training for 4 weeks (12 times treatments). Results: The results of this study after Shapiro Wilk normality test obtained normal distribution data (p >0.05), then carried out hypothesis test used Paired T - Test and obtained a significant value p = 0,000 (p <0.05). The results of the data analysis from the pre test and post test showed an increase on cognitive abilities. Conclusion: This shows that there is an effect of perceptual – motor training on changes in cognitive abilities in children with mild mental retardation.